Invited to labour or participate: intra- and inter-generational distinctions and the role of capital in children's invited participation. Issue 3 (4th May 2018) - Kiili, Johanna; Larkins, Cath
ABSTRACT: This paper applies aspects of Bourdieu's conceptual toolkit related to capital, and analyses inter- and intra-generational relations of influence. Applying Bourdieu's concepts to examples of case studies from a children's parliament in Finland, and with reference to an adult resident forum, moments of continuity and disruption in the relatively stable patterns of distinction between children and adults emerge. Children in school councils (at times) are labourers for agendas set by teachers, but the children at the top of the structure's hierarchy can benefit from cultural capital and a functional capital that enables them to set agendas and direct the work of others. The political capital of the person presenting views from the participation sphere and the dominant symbolic capital of market logics appear to have a greater impact than generation on the influence participants achieve. Unquestioned acceptance of this differentiation suggests that new approaches to invited participation structures are needed.